Endometriosis in the postmanopasual period (clinical case) - I S Zakharov; L N Petrich; T N Demyanova; Yu V Vasyutinskaya; L E Fetischeva; S N Bolotova; M S Rykova; G H Dodonova (IP Berlin A.V., 2017)
The presented material describes the clinical case of newly diagnosed endometriosis in a woman who is in the postmenopausal period. The prevalence of this pathology in individuals after the onset of menopause is 2-5% with a malignancy probability of 0.9%. However, in spite of the low risk of malignancy, according to existing recommendations it is necessary to conduct operative treatment. In the presented case, a histological study confirmed the presence of endometrioid tissue in the macro preparation.